PTU-044 Hepatic/endothelial cell co-culture; establishing optimal conditions for liver tissue engineering. (28th May 2012) - Navarro, M; Nelson, L; Burgess, K; Tura, O; Samuel, K; Plevris, J
Abstract : Introduction: Development of 3D hepatic organoids utilising human cell derivatives for in vitro drug testing and bioartificial liver support systems is challenging. Tissue engineering thick, complex structures such as human liver organoids (micro-tissue; >500 mm) will require vascularisation of 3D cultures—coupled with biomatrix support scaffolds—to both maintain integrity and promote formation of endothelial channels (sinusoid-like structures) to facilitate oxygen and nutrient transfer to hepatocytes in 3D culture. Key challenges involve directing nascent microvessels into an appropriate environment defined prominently by heterotypic cell–cell contacts and meeting high metabolic demands. In this preliminary study, we aimed to optimise heterotypic co-culture of either H uman U mbilical V ein E ndothelial C ells (HUVECs) or E ndothelial O utgrowth C ells (EOCs) with hepatic C3A cells, using appropriate biomatrix scaffolds. Methods: Different ratios of HUVECs: C3A or EOCs:C3A to form co-cultures were studied using contrast/confocal microscopy and flow cytometry following appropriate immunostaining. Flow cytometry was used to study integrin expression (Cd49a, Cd49b, Cd49f, Cd49e), endothelial markers (CD31) and EpCam, as an hepatic marker. Fingerprint unbiased metabolomics analysis was used to assess function of co-cultured cells. Matrigel and MaxGel (Sigma) were tested as candidate bioscaffolds and were compared with standard 2D cultures on plastic and collagen for each cell line as controls. Results: A ratio 3:1 (HUVECs:C3A) was optimal for growth using endothelial culture medium (Lonza EGM-2 medium, UK). Cell phenotype was maintained for 7 days in co-culture with strong integrin (Cd49a, Cd49b, Cd49f, Cd49e), and CD31 expression on HUVECs and EpCam on C3A cells, while a reduction of HUVEC cell number was noted with a parallel increase of C3A cells by day 7—to form more sheet-like structures in co-culture. Metabolomics analysis of culture media showed enhanced urea cycle, lipid synthesis and amino acid utilisation of C3A cells in co-culture. Matrigel promoted formation of microvessel structures, with interconnected channels, in both EOCs and HUVECs; and was superior to MaxGel. MaxGel in 3D sandwich culture promoted differentiated (cuboidal) morphology of C3As, but not EoCs. Conclusion: Optimisation of both cell ratios and cell numbers, as well as selection of appropriate culture media are critical factors in developing a successful hepatic co-culture system with the ability to form sinusoid-like/microvessel structures. This study represents an early step towards understanding the requirements of vascularised liver tissue for future clinical/pharmaceutical applications. Competing interests: None declared.